A place I could call my own: Queer Malays and the meanings of ‘home’ - Collin, Jerome (Routledge, 2020)
This article explores the meanings of ‘home’ for queer Malays in Malaysia through an analysis of the central gay Malay male character in Azwan Ismail’s story, Tiada sesalan (No regrets). Drawing upon studies of home by feminist and queer geographers, the article examines the character’s notions of ‘home’ and how these notions are constructed across time and space. The findings show that ‘home’ has been conceived of in many ways: as (1) a material-imaginative space; (2) a site of identity and power; and (3) a multi-scalar construct. The character has, for the most part of his life, been engaged in the process of queering home through which he developed a queer sense of ‘home’ and identity. This, however, has not been an easy task because the home is a powerful site that can both facilitate and complicate the process.